2018
DOI: 10.1111/aogs.13350
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of vaginal support structure before and after Vecchietti procedure in women with Mayer–Rokitansky–Küster–Hauser syndrome

Abstract: The preoperative presence of pelvic support structures into which the vagina is lengthened by the surgery likely explains the uncommon occurrence of vaginal prolapse in women who had the Vecchietti procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
(32 reference statements)
0
5
0
1
Order By: Relevance
“…Scar tissue at the apex as a result of the peritoneal tunneling during the Vecchietti procedure might enforce apical support of both cardinal and uterosacral ligaments. Missing scar tissue can explain why prolapse has been described quite often after self-dilatation [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Scar tissue at the apex as a result of the peritoneal tunneling during the Vecchietti procedure might enforce apical support of both cardinal and uterosacral ligaments. Missing scar tissue can explain why prolapse has been described quite often after self-dilatation [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Even though ovarian cell donors and in vitro fertilization can be carried out, the patient may still feel depressed. In patients with vaginal agenesis, surgery is also needed so that they can have sexual intercourse with partners [11] .…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, the presence of intraluminal blood or adenomyosis on MRI suggests functioning endometrium in a rudimentary uterus. However, this does not affect fertility because fertility in patients with MRKH will also be disrupted [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with vaginal agenesis also had near-normal sexual function and satisfactory sexual experiences after treatment according to the postoperative FSFI evaluations. Huebner et al ( 24 ) also suggested psychological counseling as part of the treatment plan for patients with MRKHS. Most patients with congenital absence of the vagina are mentally distressed due to the physical defect ( 25 ).…”
Section: Discussionmentioning
confidence: 99%